UPAYA MENINGKATKAN LAYANAN BIMBINGAN BELAJAR UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK - Sukarlo Manik (JURNAL PENA EDUKASI, 2020)
Abstract: The objectives of this study were: (1) To find out how to improve the learning activities of students in class VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat 2018/2019 academic year; (2) How big is the effect of tutoring on the learning activities of students in class VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat 2018/2019 academic year. The learning improvement procedure includes the implementation of classroom action research in 2 cycles. In the first cycle of the 6 categories observed in the tutoring service, only 2 were included in the "Good Enough" category, namely: (1) Listening to / paying attention to teacher explanations, (2) Students' interest in learning, when using tutoring, while 4 activities students are still in the "Not Good" category, namely: (1) active in asking, (2) asking the teacher, (3) discussing with friends, and (4) concluding the function and purpose of the service. In the second cycle of the 6 categories observed in the tutoring service, only 4 student activities were included in the "Good" category, namely: (1) Listening to / paying attention to the teacher's explanation, (2) Students' interest in learning, (3) asking the teacher, and (4) discussing with, while 2 student activities are still in the "Good Enough" category, namely: (1) active in asking, and (2) concluding the function and purpose of the service.Keywords: counseling guidance; tutoring servicesAbstrak: Tujuan penelitian ini adalah: (1) Untuk mengetahui cara meningkatkan aktivitas belajar peserta didik di kelas VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat tahun pelajaran 2018/2019; (2) Seberapa besar pengaruh bimbingan belajar terhadap aktivitas belajar peserta didik di kelas VIII SMP Negeri 2 Sei Kepayang Kec. Sei Kepayang barat tahun pelajaran 2018/2019. Prosedur perbaikan pembelajaran meliputi kegiatan pelaksanaan penelitian tindakan kelas dalam 2 siklus. Pada siklus I dari 6 kategori yang diamati dalam layanan bimbingan belajar hanya 2 yang masuk dalam kategori â€œCukup Baikâ€ yaitu: (1) Mendengarkan/memperhatikan penjelasan guru, (2) Ketertarikan peserta didik untuk belajar, bila menggunakan bimbingan belajar, sedangkan 4 aktivitas siswa masih dalam kategori â€œKurang Baikâ€ yaitu: (1) aktif dalam bertanya, (2) bertanya pada guru, (3) berdiskusi dengan teman, dan (4) menyimpulkan fungsi dan tujuan layanan. Pada siklus II dari 6 kategori yang diamati dalam layanan bimbingan belajar hanya 4 aktivitas siswa yang masuk dalam kategori â€œBaikâ€ yaitu: (1) Mendengarkan/memperhatikan penjelasan guru, (2) Ketertarikan peserta didik untuk belajar, (3) bertanya pada guru, dan (4) berdiskusi dengan, sedangkan 2 aktivitas siswa masih dalam kategori â€œCukup Baikâ€ yaitu: (1) aktif dalam bertanya, dan (2) menyimpulkan fungsi dan tujuan layanan.Kata kunci: bimbingan konseling; layanan bimbingan belajar